Metabolic Acidosis and Cardiovascular Disease in Patients on Peritoneal Dialysis - D. Raikou, Vaia; Evaggelatou, Anastasia; Kyriaki, Despina (Journal of Hypertension and Cardiology, 2016)
Backgroud: Metabolic acidosis, a common condition particularly in end stage renal disease patients, results in malnutrition and inflammation. In this study, we focused on the importance of metabolic acidosis on manifestations of cardiovascular disease in patients on peritoneal dialysis. Methods: We studied 20 patients on continuous ambulatory peritoneal dialysis (CAPD), 15 males and 5 females, on mean age 61.6 ±11.3 years old. Metabolic acidosis was determined by serum bicarbonate concentrations less than 22mmol/L, which were measured in gas machine. Dialysis adequacy was defined by total Kt/V/week for urea including peritoneal Kt/V for urea and residual GFR (ml/min/1.73m2). High sensitivity C-reactive protein (hsCRP) was measured using enzyme linked immunoabsorbed assay (ΕLISA). The concentrations of intact-parathormone (i-PTH) and beta2-microglobulin (beta2M) were measured by radioimmunoassays. Arterial stiffness was measured as carotid-femoral pulse wave velocity (c-f PWV) and augmentation index (AIx). We built a Cox regression analysis to predict coronary artery disease (CAD), congestive heart failure (CHF) and peripheral vascular disease (PVD). Results: Serum bicarbonate levels were inversely associated to beta2M, i-PTH and AIx (r=-0.451, p=0.04, r=-0.477, p=0.03 and r=-0.569, p=0.009 respectively). Cox- regression analysis revealed significant association of serum bicarbonate levels and PVD having as confounders traditional and specific for these patients risk factors. Conclusion: Metabolic acidosis may be an independent risk factor for arterial stiffening and peripheral vascular disease manifestation in patients on peritoneal dialysis.
Keywords: peritoneal dialysis; metabolic acidosis; cardiovascular disease; beta2-microglobulin.